2013
DOI: 10.1021/am402237g
|View full text |Cite
|
Sign up to set email alerts
|

Composite PLGA/AgNpPGA/AscH Nanospheres with Combined Osteoinductive, Antioxidative, and Antimicrobial Activities

Abstract: The global rise in the resistance of pathogens to conventional antibiotics has created an intensive search for alternative materials with antimicrobial properties. This study is performed with an intention to investigate the combined effects of poly(L-glutamic acid)-capped silver nanoparticles (AgNpPGA) and ascorbic acid (AscH) encapsulated within freeze-dried poly(lactide-co-glycolide) (PLGA) nanospheres to obtain a nanomaterial with simultaneous osteoinductive, antioxidative, and prolonged antimicrobial prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 43 publications
1
26
0
Order By: Relevance
“…Metal and metalloid nanoparticles are used in various biomedical applications. For example, silver, gold and platinum are some of the alternative inorganic materials with antimicrobial properties [25]. Selenium nanoparticles have also been reported to possess antibacterial as well as antiviral activities [26].…”
Section: Introductionmentioning
confidence: 99%
“…Metal and metalloid nanoparticles are used in various biomedical applications. For example, silver, gold and platinum are some of the alternative inorganic materials with antimicrobial properties [25]. Selenium nanoparticles have also been reported to possess antibacterial as well as antiviral activities [26].…”
Section: Introductionmentioning
confidence: 99%
“…Spherical nanoparticles of the poly (D,L-lactide-co-glycolide) (PLGA) were produced using physicochemical method with solvent/non-solvent systems (Stevanović et al 2007a;Stevanović et al 2007b;Stevanović et al 2007c). The encapsulation of the ascorbic acid, folic acid, silver nanoparticles (AgNp) or AgNp together with ascorbic acid in the PLGA polymer matrix have bee successfully performed by homogenization of water and organic phases (Stevanović et al2007a,b;Stevanović et al 2008a, b;Stevanović et al 2009c;Stevanović et al 2012b;Stevanović et al 2013;Stevanović et al 2014)).…”
Section: Homogenization Of Water and Organic Phasesmentioning
confidence: 99%
“…Core-shell encapsulation may be used if the polymer processing solvent is incompatible with the drug to be encapsulated while promoting bone healing [ 123 ]. Similarly, Stevanovic et al showed that silver nanoparticles and the anti-oxidant/osteogenic factor ascorbic acid could be coincorporated into PLGA nanoparticles which could then kill E. coli and MRSA as well as promote bone formation [ 124 ], although in this case incorporation into medical devices was only suggested not tried. He et al showed that polyethylenimine nanopolyplexes containing plasmids encoding vascular endothelial growth factor (VEGF) and fi broblast growth factor (FGF) could be incorporated into fi bers scaffolds made of PEG-PLA [ 125 ].…”
Section: Co-release Of Multiple Drugsmentioning
confidence: 99%